Competing Knowledges - Wissen Im Widerstreit. - Horatschek, Anna-Margaretha. (Berlin/Boston : Walter de Gruyter GmbH, 2020)
At irregular intervals, the Abhandlungen der Akademie der Wissenschaften in Hamburg [Proceedings of the Academy of Sciences in Hamburg] will publish monographs or conference reports from subfields of the natural sciences, humanities, and social sciences researched at this interdisciplinary academy. These manuscripts will be selected based upon their contribution to solving fundamental research problems, to exploring contemporary and historical issues, or to reporting about scientific discoveries of social significance.
Intro -- Grußwort -- Acknowledgements -- Table of Contents -- From Knowledge to Knowledges: An Introduction -- Part I: Competing Knowledges on a Global Scale -- Competing Knowledges: An Indian Perspective -- Fruits of Heaven: Artistic Knowledge and the Aesthetic Order of the "New World" in Albert Eckhout's Still Lifes -- In Science We Trust: Überlegungen zum Wissen der Wissenschaften -- Part II: Disciplinary Negotiations -- The Heart of Science: Systematicity -- On Knowledge and Law: The Role of Law in the Generation and Harmonisation of Knowledge -- Innovation und Relevanz: Forschung im Gerangel widerstreitender Anforderungen -- Von der Wissensgesellschaft zur empirischen Wissenschaftstheorie -- Part III: Competing Knowledges in Politics -- Wissen und das politische System -- Zur Einlagerung hochradioaktiver Reststoffe aus ethischer und politischer Sicht: Bestandsaufnahme und Ausblick -- „It is Dangerous to Generalise About State Visits": Praktiken des Wissens in der britischen Außenpolitik des 20. Jahrhunderts -- List of Authors -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books